Riverine Ecosystem Management: Science for Governing Towards a Sustainable Future - Schmutz, Stefan; Sendzimir, Jan; Schmutz, Stefan; Sendzimir, Jan (Cham Springer Nature, 2018)
Aquatic Ecology; Ecosystem Services; Environmental Management; Freshwater Science; River Restoration; Sustainable River Management; Water Pollution
English
Keywords: Ecological science, the Biosphere; Aquatic Ecology; Ecosystem Services; Environmental Management; Freshwater Science; River Restoration; Sustainable River Management; Water Pollution